A Socialization of Eco-enzyme for Organic Waste Management to Member of PKK Tulungagungan Hamlet in Pronojiwo Village - Azizah, Laili Nur (JPMAS : Jurnal Pengabdian Masyarakat, 2026)
The issue of organic waste management in Indonesia remains a critical challenge, particularly in rural areas where waste handling practices often involve indiscriminate disposal, burning, or burying, leading to significant environmental risks. In response, a community service initiative was implemented by the 2025 Collaborative Community Service Program (KKN) team from the University of Jember in Tulungagungan Hamlet, Pronojiwo Village, aiming to improve community knowledge and skills in managing household organic waste. The program introduced eco-enzyme production, a fermentation-based process using organic kitchen waste, sugar, and water to create a multifunctional product that serves as a natural cleaner, organic fertilizer, and botanical pesticide. Employing a Participatory Action Research (PAR) approach, the activity was conducted in three stages: (1) preparation, including coordination with local authorities, licensing, scheduling, and procurement of materials;(2) implementation, involving trial production, the creation of educational materials, and hands-on training through demonstration; and (3) evaluation, using a question-and- answer format to assess participants’ understanding. Results indicated substantial improvement in participants' comprehension and technical skills, enabling them to independently produce eco-enzyme while recognizing its environmental and economic benefits. The program not only promoted environmental awareness and waste reduction but also opened opportunities for household-level creative economic activities. Sustainability of the initiative is recommended through ongoing technical support, provision of necessary equipment, and integration into PKK's routine activities. Keywords: Eco-enzyme Organic waste management Community empowerment PKK Pronojiwo Village